Mortality of Elderly Patients in Ontario after Hospital Admission for Chronic Obstructive Pulmonary Disease - Jason X Nie; Li Wang; Ross EG Upshur (Canadian Respiratory Journal)
BACKGROUND: Chronic obstructive pulmonary disease (COPD) is associated with significant mortality. It is currently the fourth leading cause of death in Canada and the world.